Synopsis of lectures from the discipline «Exploitative materials» : full-time students in the specialty 274 «Motor vehicle transport» by educational and qualification level – bachelor - Nahluk, M. (Харківський національний автомобільно-дорожній університет, 2025)
The abstract outlines the basics of the technology for the production of operating materials, the requirements for them, the main properties and methods of testing materials. The main varieties, types and brands of fuels, operating materials and technical fluids used in the operation and maintenance of vehicles are given. Intended for bachelors of all forms of study according to the educational program «Motor vehicle transport».
Keywords: production technology of operating materials; automotive gasolines, diesel fuels; alternative fuels; motor oils; structural and repair materials; технологія виробництва експлуатаційних матеріалів; автомобільні бензини; дизельні палива; альтернативні палива; моторні оливи; конструкційно-ремонтні матеріали; 629.33(07)